Unravelling drivers of the future Mediterranean precipitation paradox during cyclones - Marco Chericoni; Giorgia Fosser; Emmanouil Flaounas; Marco Gaetani; Alessandro Anav (npj Climate and Atmospheric Science)
Both global climate models and a high-resolution atmosphere-ocean coupled regional climate model project a drying trend across the Mediterranean region, alongside an increase in cyclone-related precipitation. However, only the high-resolution model captures the physical mechanisms driving these changes across three emission scenarios, namely, enhanced moisture transport processes fuelling cyclone activity. These results highlight the added value of fine-scale modelling for understanding future Mediterranean hydroclimatic extremes.